Neutralizing software piracy - Chang, Victoria Munn Cheng (2019)
With our heavy reliance on modern technologies, software piracy has become an increasingly prevalent issue. Despite the real economic consequences of software piracy, few regard it as a serious crime. Extensive research has been dedicated to understanding the profile of a typical pirate and previous research has also explored how traditional criminology theories such as the neutralization theory, can be used to explain this crime. The aims of this study are twofold: (i) to examine the relationship between software piracy intentions and neutralization techniques and (ii) to better explain the gender gap in software piracy intentions by employing the neutralization theory. Survey results were obtained from 231 respondents and multiple linear regression was used to analyze the data. Covariates such as age, social adversity, baseline offending and race, were also accounted for. Further mediation analyses were conducted to better understand the role of neutralization techniques in the relationship between gender and software piracy intent. Significant, positive linear regressions were found for all the neutralization techniques. This signifies that neutralization techniques do play a part in determining one’s intention to pirate software. Mediation analyses also found that three techniques: (i) denial of injury, (ii) condemnation of condemners and (iii) defense of necessity, played a significant role in explaining the gendered differences in software piracy intentions. The study findings help provide new insights into the decision mechanisms behind a person’s intent to pirate software. These results can be used to help formulate more effective and targeted interventions aimed at reducing piracy.